2019
DOI: 10.2147/jpr.s228255
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ameliorative Effects Of N-Acetylcysteine As Adjunct Therapy On Symptoms Of Painful Diabetic Neuropathy</p>

Abstract: PurposePainful diabetic neuropathy (PDN) is a variant of diabetic peripheral neuropathy which is highly prevalent and distressing in diabetic patients. Despite its high burden, the optimal treatment of PDN has remained a clinical challenge. To explain the emergence and maintenance of PDN, increasing attention has been focused on dimensions of inflammation and oxidative toxic stress (OTS). Accordingly, the aim of this study was to investigate the effects of oral N-acetylcysteine (NAC), an agent with known anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 76 publications
1
24
0
1
Order By: Relevance
“…Finally, nitric oxide reduces receptor thresholds, resulting in peripheral and central sensitization [ 93 ], and the inhibitory activity of the central nervous system, leading to central sensitization of the dorsal horn neurons [ 94 ]. In line with the above observations, oxidative stress has also been associated to chronic pain and proposed to be a possible contributor to the maintenance of pain symptoms [ 20 , 84 , 95 , 96 ]. While both inflammatory and oxidative processes cover a role in the acute nociceptive phase, it is mainly the production of ROS that seems to account for the maintenance of nociceptive processes in the chronic phase [ 97 ].…”
Section: Oxidative Stress Contributes To Painmentioning
confidence: 66%
“…Finally, nitric oxide reduces receptor thresholds, resulting in peripheral and central sensitization [ 93 ], and the inhibitory activity of the central nervous system, leading to central sensitization of the dorsal horn neurons [ 94 ]. In line with the above observations, oxidative stress has also been associated to chronic pain and proposed to be a possible contributor to the maintenance of pain symptoms [ 20 , 84 , 95 , 96 ]. While both inflammatory and oxidative processes cover a role in the acute nociceptive phase, it is mainly the production of ROS that seems to account for the maintenance of nociceptive processes in the chronic phase [ 97 ].…”
Section: Oxidative Stress Contributes To Painmentioning
confidence: 66%
“…Likewise, animal studies investigating retinopathy [ 69 ] and diabetic nephropathy [ 70 ] show promising results. Recently, a study in humans has shown significant benefit in painful peripheral neuropathy [ 71 ]. Patients with painful neuropathy improved over 8 weeks with the use of NAC (600 mg bid) as adjuvant therapy to pregabalin.…”
Section: Metabolic Syndrome Including Nonalcoholic Fatty Liver Disease Diabetes and Polycystic Ovarymentioning
confidence: 99%
“…Beyond this, recent research has revealed that NAC may also have antinociceptive and analgesic effects; surprisingly enough, favorable effects of NAC supplementation in various types of chronic pain syndromes have been demonstrated in a number of clinical studies 23 . Although the precise mechanism by which NAC exerts its antinociceptive and analgesic effect is not known; it is suggested that it also may be related to its anti‐inflammatory and antioxidant actions 19,38‐41 . Thus, NAC, through its antinociceptive and analgesic activities, may also be able to relieve the pain symptoms associated with CP/CPPS.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that NAC could significantly decrease the plasma level of pro‐inflammatory biomarkers such as tumour necrosis factor alpha (TNF‐α) that have an essential role in prostate inflammation 18 . Further, emerging data suggest that NAC supplementation may also be helpful in managing several chronic pain conditions, in particular neuropathic pains 18‐20 . So, considering the probable neuropathic nature of pain associated with CP/CPPS, 12,13 NAC treatment may also alleviate pain in patients affected with CP/CPPS.…”
Section: Introductionmentioning
confidence: 89%